Increase of ATP-sensitive potassium (KATP) channels in the heart of type-1 diabetic rats - Chen Zhih-Cherng; Cheng Yung-Ze; Chen Li-Jen; Cheng Kai-Chun; Li Yin-; Cheng Juei- (Cardiovascular Diabetology, 2012)
Abstract Background An impairment of cardiovascular function in streptozotocin (STZ)-diabetic rats has been mentioned within 5 days-to-3 months of induction. ATP-sensitive potassium (KATP) channels are expressed on cardiac sarcolemmal membranes. It is highly responsive to metabolic fluctuations and can have effects on cardiac contractility. The present study attempted to clarify the changes of cardiac KATP channels in diabetic disorders. Methods Streptozotocin-induced diabetic rats and neonatal rat cardiomyocytes treated with a high concentration of glucose (a D-glucose concentration of 30 mM was used and cells were cultured for 24 hr) were used to examine the effect of hyperglycemia on cardiac function and the expression of KATP channels. KATP channels expression was found to be linked to cardiac tonic dysfunction, and we evaluated the expression levels of KATP channels by Western blot and Northern blot analysis. Results The result shows diazoxide produced a marked reduction of heart rate in control group. Furthermore, the methods of Northern blotting and Western blotting were employed to identify the gene expression of KATP channel. Two subunits of cardiac KATP channel (SUR2A and kir 6.2) were purchased as indicators and showed significantly decreased in both diabetic rats and high glucose treated rat cardiac myocytes. Correction of hyperglycemia by insulin or phlorizin restored the gene expression of cardiac KATP in these diabetic rats. Conclusions Both mRNA and protein expression of cardiac KATP channels are decreased in diabetic rats induced by STZ for 8 weeks. This phenomenon leads to result in desensitization of some KATP channel drugs.